Martha E. Sánchez. A Translational Turn: Latinx Literature into the Mainstream. U of Pittsburg P, 2018. - Belen Rodríguez Mourelo (Studies in 20th & 21st Century Literature, 2021)
Review of Martha E. Sánchez. A Translational Turn: Latinx Literature into the Mainstream. U of Pittsburg P, 2018. xiv +178 pp.
Keywords: Latinx Literature; mainstream; translation